Green light to an integrative view of Microscolex phosphoreus (Dugès, 1837) (Annelida: Clitellata: Acanthodrilidae) - Rota, Emilia; Martinsson, Svante; Erséus, Christer; Petushkov, Valentin N.; Rodionova, Natalja S.; Omodeo, Pietro (Zootaxa, 2018)
The small synanthropic and peregrine earthworm Microscolex phosphoreus (Dugès, 1837) is reported for the first time from Siberia. Morphological and DNA barcode (COI) analyses of this and widely separate samples worldwide demonstrate that, as currently identified, M. phosphoreus is a heterogeneous taxon, with divergent lineages occurring often in the same locality and hardly providing geographically structured genetic signals. The combined morphological and genetic evidence suggests that at least four of the found clades should be reclassified as separate species, both morphologically and genetically distinct from each other. However, as the specimen number was limited and only the COI gene was studied for the genetic work, we hesitate in formally describing new species. There would also be the problem of assigning the available names to specific lineages. Our findings encourage careful external and anatomical examination and using reliable characters such as the interchaetal distances and spermathecal morphology for correct identification and for deeper evaluation of cryptic diversity in this interesting bioluminescent worm.